2023
DOI: 10.1158/1078-0432.ccr-22-3493
|View full text |Cite
|
Sign up to set email alerts
|

Learning Individual Survival Models from PanCancer Whole Transcriptome Data

Abstract: Purpose: Personalized medicine attempts to predict survival time for each patient, based on their individual tumour molecular profile. We investigate whether our survival learner in combination with a dimension reduction method can produce useful survival estimates for a variety of cancer patients. Experimental Design: This paper provides a method that learns a model for predicting the survival time for individual cancer patients from the PanCancer Atlas: given the (16335-dimensional) gene expression profiles … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This study presents a survival modelling perspective called individual survival distributions with the MTLR model to provide novel insight into personalized survival predictions of gastric adenocarcinoma. Prior research has demonstrated that ISDs provide a valuable alternative to popular personalized survival modelling strategies, such as nomograms [12,15]. Using MTLR, we identified that the TME score and chemotherapy provide non-proportional but similar survival effects over time.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This study presents a survival modelling perspective called individual survival distributions with the MTLR model to provide novel insight into personalized survival predictions of gastric adenocarcinoma. Prior research has demonstrated that ISDs provide a valuable alternative to popular personalized survival modelling strategies, such as nomograms [12,15]. Using MTLR, we identified that the TME score and chemotherapy provide non-proportional but similar survival effects over time.…”
Section: Discussionmentioning
confidence: 98%
“…MTLR generates individual patient survival distributions for a specific number of times based on the number of uncensored patients in a dataset [26]. An empirical study demonstrated that MTLR provided equivalent or superior discrimination compared to other survival models and provided excellent model calibration in both low-and high-dimensional datasets [12,15,18].…”
Section: Models and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation